Exploring Utterance and Cognitive Fluency of L1 and L2 English Speakers: Temporal Measures and Stimulated Recall. Issue 4 (15th October 2014) - Kahng, Jimin
<x xml:space="preserve">Abstract</x> Although fluency constitutes an essential component of second language (L2) proficiency, there are mixed results and gaps in the literature on how L2 speakers' fluency differs from fluent speech production in a first language (L1). The research reported in this article investigated utterance fluency and cognitive fluency of L1 English speakers and Korean learners of L2 English by eliciting and comparing quantitative evidence from temporal measures and qualitative evidence from stimulated recall responses. In addition, the L2 speaker group's proficiency was measured by an in‐house institutional test so as to inspect how L2 fluency measures correlated to varying proficiency. The L1 and L2 speakers were different in speed, length of run, and silent pauses. In particular, a striking group difference in silent pause rate within a clause was found, consistent with the claim that pauses within clauses reflect processing difficulties in speech production. Different qualitative patterns in the stimulated recall responses by the lower and higher proficiency learners are discussed in relation to Ullman's declarative/procedural model and Segalowitz's fluency vulnerability points in L2 speech production.